2018
DOI: 10.3390/ijgi7110442
|View full text |Cite
|
Sign up to set email alerts
|

Complying with Privacy Legislation: From Legal Text to Implementation of Privacy-Aware Location-Based Services

Abstract: An individual's location data is very sensitive geoinformation. While its disclosure is necessary, e.g., to provide location-based services (LBS), it also facilitates deep insights into the lives of LBS users as well as various attacks on these users. Location privacy threats can be mitigated through privacy regulations such as the General Data Protection Regulation (GDPR), which was introduced recently and harmonises data privacy laws across Europe. While the GDPR is meant to protect users' privacy, the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Ataei et al examine the GDPR legislation in depth to understand how certain aspects can be implemented using user interfaces(UI), and analyze how best to comply with GDPR regulation [59]. Consequently, Ataei et al defined a set of guidelines for Location Based Service(LBS) design and development, with the goal of making it easier for developers to create systems that are GDPR compliant.…”
Section: B Analysis Of Location Privacy Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ataei et al examine the GDPR legislation in depth to understand how certain aspects can be implemented using user interfaces(UI), and analyze how best to comply with GDPR regulation [59]. Consequently, Ataei et al defined a set of guidelines for Location Based Service(LBS) design and development, with the goal of making it easier for developers to create systems that are GDPR compliant.…”
Section: B Analysis Of Location Privacy Lawsmentioning
confidence: 99%
“…Both Georgiadou et al [55] Ataei et al [59] and studies provide a thorough analysis of GDPR policy as it affects location. Georgiadou et al [55] uses this analysis to encourage privacy legislation developments in the African Union while Ataei et al [59] uses the analysis of the GDPR to help produce usable UI.…”
Section: B Analysis Of Location Privacy Lawsmentioning
confidence: 99%
“…There are some studies that deal with challenges that come with GDPR. Ataei et al (2018a) identified three challenges with GDPR, after interviewing six GDPR experts. The first is user-friendliness-implementing GDPR in a way that does not place unmanageable burdens on users.…”
Section: Research State Of the Artmentioning
confidence: 99%
“…As mentioned in the introduction, there have been some theoretical evaluations in the literature where GDPR has been compared to its predecessor, DIR95 (Ataei et al 2018a;Grundstrom et al 2019;Tikkinen-Piri et al 2017). Ataei et al (2018a) has their focus on the user interface level for Location-Based Services rather than issues that SMEs face. Grundstrom et al (2019) focuses on challenges for the organisation in a specific sector, insurance.…”
Section: Theoretical Evaluationmentioning
confidence: 99%
“…Users utilize LBSs to find points of interests, navigate the destination, and inquire public transportation etc. [1][2][3][4][5][6]. In all of these requested services, users need to disclose their location information to the location-based service provider (LBSP).…”
Section: Introductionmentioning
confidence: 99%